Beyond Environmental Concern: Attitude and Value in Suboptimal Food Purchase Intention - Nila Marita Indreswari; Ali Hanafiah (Annals of Management and Organization Research, 2026)
Purpose: Food waste remains a pressing sustainability challenge, particularly in emerging markets where suboptimal food is frequently rejected due to aesthetic imperfections. This study examines how Attitude mediates the effects of Environmental Concern, Moral Norms, Perceived Value, and Unappealing Appearance on purchase intention toward suboptimal food among millennials in Indonesia. Research Methodology: A quantitative survey was conducted with 500 millennial respondents residing in Java Island. Data were analyzed using Structural Equation Modelling–Partial Least Squares (SEM-PLS) to assess the effects of Environmental Concern, Moral Norms, Perceived Value, and Unappealing Appearance on purchase intention, with Attitude as a mediating variable. Results: The results demonstrate that Perceived Value is the strongest determinant of Attitude and Purchase Intention, while environmental concern exerts no significant effect, indicating a clear attitude–behavior gap. Unappealing Appearance negatively influences Attitude but does not directly reduce purchase intention. Attitude fully mediates this relationship, suggesting a cognitive override mechanism in which rational evaluation mitigates aesthetic aversion. Conclusions: Purchase Intention toward suboptimal food is primarily shaped by value-based evaluation and Attitude formation rather than general environmental awareness. These findings highlight the central role of instrumental and psychological mechanisms in driving sustainable consumption in emerging markets. Limitations: The study focuses on millennials in Java Island and measures Purchase Intention instead of actual purchasing behavior. Contributions: This study integrates the Theory of Planned Behavior and the Stimulus–Organism–Response framework to explain sustainable food consumption in an emerging market context and provides practical insights for policymakers and food retailers.